If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x=4(3-2)+6/8
We simplify the equation to the form, which is simple to understand
x=4(3-2)+6/8
Simplifying:
x=4*(3-2) + 0.75
Simplifying terms in parentheses
x=4*(+1) + 0.75
Reorder the terms in parentheses
x=+(+4) + 0.75
Remove unnecessary parentheses
+x=+4 + 0.75
We move all terms containing x to the left and all other terms to the right.
+1x=+4 + 0.75
We simplify left and right side of the equation.
+1x=+4.75
We divide both sides of the equation by 1 to get x.
x=4.75
| 3m-2(m-1)+11=16 | | 15p^4+61p^3q+4p^2q^2= | | 4c+8=-55+3c | | -3(m-3)= | | P+7p-5p= | | 8(3m+7)= | | p-24=13 | | 12x-32=8x | | 7(2m-3)= | | 12x+(-352/7)=20 | | 1/4(4m-8)= | | 3=(4x+1)(x-7) | | r^2-12r=-35 | | 1/2(m-2)= | | 14+2x=1.50+20x | | 6(m-5)= | | 3(x+1)=-3(2x-4)+9 | | b-16=7 | | -8x^2=-48x+128 | | 4x^2-11=-20x | | -1y+8=3y+4 | | 3(m-5)= | | 16n^2-49=0 | | 7(m-3)= | | 29+x=-36 | | -48x+128=-8x^2 | | 7+4x=2-x+10 | | 0.5(x-8)=0.2x+11 | | 3x^2+12x-16=0 | | 8=-16c | | 1y+8=3y+4 | | M(x)=20x-x^2 |